2017
DOI: 10.3390/su9050833
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Medium- and Long-Term Global Energy Prospects and Scenarios

Abstract: Abstract:The paper presents recent and future trends of the world energy market, as highlighted by medium-and long-term projections. Energy demand and energy consumptions projected by IEA (International Energy Agency) are examined, in comparison with projections provided by other international agencies and companies in the energy sector. In particular, energy resources, energy consumption and economic growth both in developing and developed countries are presented, with a particular attention to the role of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In the Middle East, Saudi Arabia was studied by [175], and finally, [176] proposed to investigate quantitatively the impact of public policy of gradual reduction in fossil fuel consumption given through government subsidies; the results indicate that this contributes positively to the performance of macroeconomic factors [176]. In non-quantitative approaches, [177] investigated trends for the global energy market in the medium and long term and concluded that there is a global interest in renewable and non-conventional energies, as well as in improving energy efficiency to reduce an environmental impact on energy generation [177]. Europe was studied by [178,179], while China was studied by [180,181], Russia by [182], the economies of Mexico and Vietnam by [183] and Nigeria in [184].…”
Section: Discussionmentioning
confidence: 99%
“…In the Middle East, Saudi Arabia was studied by [175], and finally, [176] proposed to investigate quantitatively the impact of public policy of gradual reduction in fossil fuel consumption given through government subsidies; the results indicate that this contributes positively to the performance of macroeconomic factors [176]. In non-quantitative approaches, [177] investigated trends for the global energy market in the medium and long term and concluded that there is a global interest in renewable and non-conventional energies, as well as in improving energy efficiency to reduce an environmental impact on energy generation [177]. Europe was studied by [178,179], while China was studied by [180,181], Russia by [182], the economies of Mexico and Vietnam by [183] and Nigeria in [184].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change and environmental concerns further impact energy usage, highlighting the need for continuous monitoring to adapt to shifts in demand related to weather variations and policy changes [94]. As consumer preferences evolve and global energy consumption rises, particularly in developing nations, forecasting models must incorporate these changes to remain effective [95,96]. Economic fluctuations and geopolitical events can significantly affect energy consumption, emphasizing the importance of continuous monitoring for accurate predictions [97][98][99].…”
Section: Continuous Monitoring and Adaptationmentioning
confidence: 99%
“…With the continuous development of science and technology, the types of energy available for human use are not limited to traditional fossil fuels (coal, oil, and natural gas) . Wind energy, solar energy, geothermal energy, biomass energy, hydrogen energy, and other green, coordinated, and sustainable energy types are increasingly appearing in people’s daily lives. In 2013, fossil fuels accounted for 81% of global primary energy consumption. , It is estimated that, by 2040, oil and natural gas will still occupy the world’s major energy markets . As an unconventional fossil energy rich in natural gas, natural gas hydrate (NGH) has attracted the attention of more and more scientists. , …”
Section: Introductionmentioning
confidence: 99%